2017
DOI: 10.1016/j.pharep.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and anti-nociceptive effects of strontium ranelate on the zymosan-induced temporomandibular joint inflammatory hypernociception in rats depend on TNF-α inhibition

Abstract: Strontium ranelate may achieve its antinociceptive effects through the reduction of TNF-α levels in the trigeminal ganglion, but not suppressing IL-1β expression nor inducing the HO-1 pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
2
9
0
1
Order By: Relevance
“…SrRan (0.5, 5, and 50 mg/kg/day) also exhibited antinociceptive effects on the temporomandibular joint of rats in a zymosan-induced model of OA by reducing hypernociception, assessed using the Von Frey test. This phenomenon was verified, for the first time, in the present study at doses of 500 mg/kg/day, probably because the magnitude of OA induced in the knee was different from that induced in the temporomandibular joint ( Alves et al, 2017 ). This was also verified at 300 mg/kg/day but not at 30 mg/kg/day in zymosan-induced knee OA ( Nunes et al, 2015 ).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…SrRan (0.5, 5, and 50 mg/kg/day) also exhibited antinociceptive effects on the temporomandibular joint of rats in a zymosan-induced model of OA by reducing hypernociception, assessed using the Von Frey test. This phenomenon was verified, for the first time, in the present study at doses of 500 mg/kg/day, probably because the magnitude of OA induced in the knee was different from that induced in the temporomandibular joint ( Alves et al, 2017 ). This was also verified at 300 mg/kg/day but not at 30 mg/kg/day in zymosan-induced knee OA ( Nunes et al, 2015 ).…”
Section: Discussionsupporting
confidence: 75%
“…This result corroborates available data showing a reduction in synovial fluid levels of TNF-α and IL-1β in zymosan-induced OA rats treated with SrRan at a dose of 300 mg/kg/day ( Nunes et al, 2015 ). A decrease in the expression of TNF-α without changes in leukocyte count and IL-1β levels was also observed in another pre-clinical study of periarticular tissue samples, with lower doses of SrRan (up to 50 mg/kg/day) ( Alves et al, 2017 ). These results were not confirmed in a study with rats subjected to oophorectomy and treated with SrRan at doses of 300 and 625 mg/kg/day, with no reduction of TNF-α and MMPs, which are metal-dependent endopeptidases that remodel the extracellular matrix ( Mierzwa et al, 2017 ).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Here, we showed that S. maritima (5 mg/kg) significantly increased IL-10 gingival levels, an anti-inflammatory cytokine, while decreasing the pro-inflammatory cytokines TNF-α and CINC-1. Alternative therapeutic approaches based that inhibit TNF-α production have been successfully used for the pre-clinical and clinical treatment of chronic inflammatory diseases, particularly rheumatoid arthritis and temporomandibular joint disorders (Feldmann, 2002 ; Araújo et al, 2013 ; Freitas et al, 2016 ; Alves et al, 2017 ). Further, when mRNA expression for TNF-α, IL-1β, iNOS, and RANK were evaluated, S. maritima 5 mg/kg significantly reduced mRNA expression for all these genes compared to the vehicle group.…”
Section: Discussionmentioning
confidence: 99%